KNOWLEDGE AND ATTITUDE OF PEOPLE TOWARDS ORGAN DONATION - Nahida Khan; Zahid Masood; Sabeeka Zahra (Journal of University Medical & Dental College)
ABSTRACT Objective: Study and analyze the knowledge and attitude of people towards organ donation among adult population. Study design: A cross sectional study. Setting and duration: The study was conducted from 1st May 2011 to 30th June 2011 in the Madina Teaching Hospital Faisalabad by interviewing the people visiting the hospital as attendants. Materials and methods: Primary data containing sample size of 200 was collected through convenience sampling. A predesigned close ended questionnaire was used to collect data through face-to-face interaction with people at Madina Teaching Hospital, Faisalabad. For analysis of primary data SPSS version 17 was used. Results: Statistically significant association of knowledge about organ donation with education (p=0.000) and socioeconomic status (p=0.003) was observed. Attitude towards organ donation was significantly associated with age (p=0.017), education (p=0.000) and socioeconomic status (p=0.001). Majority (67.4%) of respondents thought that their religion allows organ donation and it should be promoted. Television (46%) came out as the major source of information. Only 27% knew about any law regulating organ donation. Lack of knowledge was seen among people regarding law for organ donation in Pakistan. 90% thought that organ donation was considered to be ethically correct. None of the respondents was actual donor. Conclusion: It can be concluded that there is a wide gap in terms of organ donation on the basis of education and socioeconomic status among the sample population. People who can donate seem to be reluctant to donate their organs to those in need (recipient) due to the lack of knowledge and fear of organ being misused. Further people who can donate organ assume that organ donation generally comes from addicts and poor people. Adequate knowledge may change the attitude of people towards organ donation. Multi-sectoral approach (e.g, electronic and print media, religious scholars, doctors and teachers) should be used to promote awareness of organ donation. Further studies are needed to motivate the general population for organ donation.